Qualitative Analysis of Transparency Efforts in Public Policy at the Village Level - Royadi, Royadi; Afnan, Dikhorir; Wildanu, Eka (Jurnal Polisci, 2023)
Qualitative Analysis of Transparency Efforts in Public Policy in Cikeduk Village, Depok District, Cirebon Regency, West Java, Indonesia. This research will explore various efforts made by Cikeduk Village officials in encouraging openness and transparency in the implementation of public policies. This research will analyze the information mechanisms provided, responses to public feedback, as well as changes in the level of government transparency and citizen participation in policy processes. Qualitative method as a research procedure that produces descriptive data in the form of written or spoken words of people and observable behavior. According to them, this approach is directed at the setting and the individual holistically. The result of this study is that public trust in the performance of the Cikeduk village apparatus is quite positive. This is marked by the sustainability of village government programs that as a whole can run smoothly. The performance of the village apparatus in providing the best service to the community is also considered reliable. The conclusion is that the village head must really be a leader for the entire community, not the leader of some groups, families, descendants, certain religions and tribes and so on. Community leader means a leader who is close to the community, protects, protects and at the same time serves his community.